A bedtime kiss for Chester Raccoon - Penn, Audrey, 1947-; Gibson, Barbara (Terre Haute, IN : Tanglewood, 2010)
When Chester the raccoon goes to bed at sunrise, the shadows cast in his room are frightening and keep him from falling asleep.
On board pages.
Keywords: Fear -- Juvenile fiction; Bedtime -- Juvenile fiction; Raccoon -- Juvenile fiction; Stories in rhyme; Fear -- Fiction; Bedtime -- Fiction; Raccoon -- Fiction; Board books